INTERACTIVE WHITEBOARDS: FROM THE PAST TO THE AGE OF ARTIFICIAL INTELLIGENCE - Baumgratz, Helen Cristina Minardi (Seven Editora, 2025)
This study addresses the use of the digital blackboard as a pedagogical support tool. The digital blackboard provides visually attractive and interactive content that helps maintain student interest, mobilizing different perception channels, such as visual, auditory, and kinesthetic. The role of the teacher in integrating this technological tool into the school environment is emphasized, adapting it to the needs of the students and observing technical and didactic principles. The research highlights the transformation introduced by artificial intelligence and machine learning, outlining a more interactive, personalized future educational landscape in line with the challenges of the 21st century. The study is bibliographic and exploratory, seeking new perspectives for subsequent investigations. DOI: https://doi.org/10.56238/sevened2025.030-075